High aspect ratio TiO2 nanotube layers obtained in a very short anodization time - Alijani, Mahnaz; Sopha, Hanna Ingrid; Ng, Siow Woon; Macák, Jan (Elsevier, 2021)
Over the past years, the growth of high aspect ratio (HAR) anodic TiO2 nanotubes in a very short time (minute scale) has remained challenging. In the present report, TiO2 nanotube (TNT) layers with HAR approximate to 450 were obtained during only 15 min of optimized anodization. The key feature is the use of NH4 F/H2O/ethylene glycol (EG) electrolytes with the addition of lactic acid (LA) that prevents the dielectric breakdown and enables anodization at higher potentials compared to the classical NH4F/H2O/EG electrolyte without LA. The thickness and average diameter of the obtained TNT layers for 15 minutes? anodization at 160 V were approximately 80 mu m and 170 nm, respectively. Furthermore, we show for the first time that high temperature anodizing, previously introduced as a driving force for the growth of HAR nanotubes in a short time, can be avoided by an accurate optimization of the anodization conditions at room temperature. The results clearly show that electrolytes containing LA can serve as a promising candidate for the ergonomic and economic production of HAR TNT layers on Ti substrates in very short anodization times, i.e. with the addition of LA, the anodization time can be significantly reduced from several hours or several days to 15-30 min. (C) 2021 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license.

Over the past years, the growth of high aspect ratio (HAR) anodic TiO2 nanotubes in a very short time (minute scale) has remained challenging. In the present report, TiO2 nanotube (TNT) layers with HAR approximate to 450 were obtained during only 15 min of optimized anodization. The key feature is the use of NH4 F/H2O/ethylene glycol (EG) electrolytes with the addition of lactic acid (LA) that prevents the dielectric breakdown and enables anodization at higher potentials compared to the classical NH4F/H2O/EG electrolyte without LA. The thickness and average diameter of the obtained TNT layers for 15 minutes? anodization at 160 V were approximately 80 mu m and 170 nm, respectively. Furthermore, we show for the first time that high temperature anodizing, previously introduced as a driving force for the growth of HAR nanotubes in a short time, can be avoided by an accurate optimization of the anodization conditions at room temperature. The results clearly show that electrolytes containing LA can serve as a promising candidate for the ergonomic and economic production of HAR TNT layers on Ti substrates in very short anodization times, i.e. with the addition of LA, the anodization time can be significantly reduced from several hours or several days to 15-30 min. (C) 2021 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license.
High aspect ratio TiO2 nanotube layers obtained in a very short anodization time
Keywords: Anodization; TiO2 nanotubes; Lactic acid; Aging; Breakdown; Anodization; TiO2 nanotubes; Lactic acid; Aging; Breakdown